2011
DOI: 10.1073/pnas.1014877108
|View full text |Cite
|
Sign up to set email alerts
|

Solar composition from the Genesis Discovery Mission

Abstract: Science results from the Genesis Mission illustrate the major advantages of sample return missions. (i) Important results not otherwise obtainable except by analysis in terrestrial laboratories: the isotopic compositions of O, N, and noble gases differ in the Sun from other inner solar system objects. The N isotopic composition is the same as that of Jupiter. Genesis has resolved discrepancies in the noble gas data from solar wind implanted in lunar soils.(ii) The most advanced analytical instruments have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…NASA Discovery Mission V, Genesis, collected solar wind in space, 1.5 million km sunward from Earth, for a period of 2.3 years and returned this sample for laboratory analysis (Burnett et al, 2003;Burnett and Team, 2011;Reisenfeld et al, 2013). The solar wind can serve as a proxy for the composition of the Sun and, thus, average of composition of the solar nebula (Marty et al, 2011;McKeegan et al, 2011), provided that fractionation processes occurring during the formation of the solar wind (e.g., Heber et al, 2012a) can be understood and quantitatively modeled.…”
Section: Introductionmentioning
confidence: 99%
“…NASA Discovery Mission V, Genesis, collected solar wind in space, 1.5 million km sunward from Earth, for a period of 2.3 years and returned this sample for laboratory analysis (Burnett et al, 2003;Burnett and Team, 2011;Reisenfeld et al, 2013). The solar wind can serve as a proxy for the composition of the Sun and, thus, average of composition of the solar nebula (Marty et al, 2011;McKeegan et al, 2011), provided that fractionation processes occurring during the formation of the solar wind (e.g., Heber et al, 2012a) can be understood and quantitatively modeled.…”
Section: Introductionmentioning
confidence: 99%
“…It is also noteworthy that Westphal et al (2014) recently reported seven contemporary interstellar grains captured by the Stardust Interstellar Dust Collector, which are the first returned interstellar dust particles. Solar-wind particles, captured by the GENESIS spacecraft (2001)(2002)(2003)(2004) (Burnett et al, 2011;Burnett, 2013), provided new interesting information on the oxygen isotopic composition of the Sun (McKeegan et al, 2011). The oxygen isotopic composition of the Sun is close to that of CAIs, which is the oldest refractory rocky components with 16 O-enriched isotopic compositions (e.g., MacPherson, 2014), but is different from most of inner solar system bodies, including the Earth.…”
Section: Introductionmentioning
confidence: 99%
“…This finding revolutionized our understanding of the Solar System. (ii) Next followed the discovery (9) of excesses of 26 Mg that formed by the in situ decay of 26 Al, a rare isotope of aluminum that has a half-life of about 0.71 my. The short half-life mandates that the 26 Al was formed very shortly before the Solar System formed, probably as a result of a nearby supernova.…”
Section: Meteorites From Marsmentioning
confidence: 99%
“…(ii) Next followed the discovery (9) of excesses of 26 Mg that formed by the in situ decay of 26 Al, a rare isotope of aluminum that has a half-life of about 0.71 my. The short half-life mandates that the 26 Al was formed very shortly before the Solar System formed, probably as a result of a nearby supernova. Finally, a few CAIs were found to have isotopic anomalies in other elements that are not the result of radioactive decay and must be traces of nucleosynthetic processes within evolved stars that, again, predated formation of our solar system.…”
Section: Meteorites From Marsmentioning
confidence: 99%
See 1 more Smart Citation